A Feasibility study on Water Fitness - Collado, Hazel Kristine M.; Cortez, Daniel Mark.; Yumul, Lemuel Eric. (Diliman, Quezon City College of Engineering, 2005)
The past few decades have been lost to the rise if health and fitness awareness. This led to the increase in fitness facilities and the corresponding increase in variety and sophistication of exercise methods. This also led to the expansion of fitness consciousness to the majority of the population. This paper examines and presents the feasibility of setting up a Water Gym facility to meet these needs. The water fitness project, which was named Water Fitness, is an innovative fitness center which centers on water exercises and water aerobics as its primary fitness tool. The paper focuses on analyzing the marketing, technical and socio-profitability of setting up the said Water Fitness establishment. Moreover, the paper studies the marketing, technical and organizational requirements of setting up the business. For the marketing aspect, surveys primarily from Social Weather Station (SWS), National Statistical Board (NSCB), National Statistics Office (NSO), Family, Income and Expenditures Survey (FIES) were combined with survey done on gym and non-gym goers to determine the demand of Water Fitness. Specifically, the exercise orientation of population was used as the key factor in determining demand. Supply was derived bu surveying a fraction of the gyms in NCR and then classifying the rest according to their level if service and by their membership size. From these data, potential customers were segmented by demographic data and also by their attitude regarding exercise. It was then determined that the relaxation and low-impact will be the competitive advantages, which will be focused on the "uninitiated believers" population. Sales was also forecasted with the various positioning strategies used. Specifically, a networking plan will be used in attracting new members into the facility. Sales data from the the data is then translated into the expected customer level at the technical study. This level is used in deriving the expected capacity that will be planned for. Equipment, material, labor, facility and utility requirements and costs are then computed from the expected capacity level. This all was consolidated in planning for a 500 m² leased Moroccan-designed facility which would contain two 60 m² heated pools, a gym area, spa and sauna. The facility was also designed to be manned by an operations manager, membership consultant, front-desk clerk, maintenance personnel and most importantly a fitness team headed by a licensed physical therapist. The costs and supplier requirements are summed up and are found to be feasible. The organizational study of the business was arranged by selecting a partnership as the form of the company. This would be funded jointly by the partners and through short-term loans from leading banks. Financial indicators are then solved. Results showed that the business performed as well as the fitness industry standard of long payback periods but low operating costs and high long-term gain. Results also reflected a pessimistic scenario due to the conservative cost estimates used throughout the project. Social-profitability study also reflected that quantitatively through income tax, employment and a positive NPV and qualitatively through improving people's health and helping ease injuries, that Water Fitness helps add value to society. Overall, the study shows that Water Fitness is viable and worthy endeavor.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Water Fitness; Physical fitness centers; Participatory monitoring and evaluation (Project management)